2021
DOI: 10.1002/ana.26089
|View full text |Cite
|
Sign up to set email alerts
|

Alpha‐Synuclein Oligomers and Neurofilament Light Chain Predict Phenoconversion of Pure Autonomic Failure

Abstract: Objective To explore the role of alpha‐synuclein (αSyn) oligomers and neurofilament light chain (NfL) in cerebrospinal fluid (CSF) of patients with pure autonomic failure (PAF) as markers of future phenoconversion to multiple system atrophy (MSA). Methods Well‐characterized patients with PAF (n = 32) were enrolled between June 2016 and February 2019 at Mayo Clinic Rochester and followed prospectively with annual visits to determine future phenoconversion to MSA, Parkinson's disease (PD), or dementia with Lewy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 42 publications
(105 reference statements)
0
53
0
Order By: Relevance
“…Likewise, out of 12 HC subjects in the tested cohort with SCOPA-AUT score ≥ 7, 2 (17%) showed positive αSyn-SAA (#3112 in Amprion Y3, and #3264 by all groups). Several studies have now noted much higher positivity rates of αSyn-SAA in prodromal cases [ 24 , 37 , 38 ]. Up to 59% of patients with RBD confirmed by polysomnography can have DAT deficit at baseline [ 39 ], vs. none in the PPMI control subjects with RBD symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, out of 12 HC subjects in the tested cohort with SCOPA-AUT score ≥ 7, 2 (17%) showed positive αSyn-SAA (#3112 in Amprion Y3, and #3264 by all groups). Several studies have now noted much higher positivity rates of αSyn-SAA in prodromal cases [ 24 , 37 , 38 ]. Up to 59% of patients with RBD confirmed by polysomnography can have DAT deficit at baseline [ 39 ], vs. none in the PPMI control subjects with RBD symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…These SWEDD subjects did have early motor signs of parkinsonism, indicating manifest nigrostriatal dysfunction, but the relative preservation of dopaminergic terminals by imaging suggests that diagnosis by αSyn-SAA may be possible before significant neuron loss. αSyn-SAA has already been tested in several cohorts of prodromal synucleinopathies, including RBD or pure autonomic failure, detecting seeding-competent αSyn forms before definite motor or cognitive phenotypes emerge [ 24 , 37 , 38 , 44 ]. Decreased binding of radioligand can indicate disruption of the nigrostriatal pathway, but this is not specific to PD or to αSyn-dependent degenerative processes, as this can be seen in other forms of parkinsonism, such as PSP or CBD.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also tried to decipher whether α-syn strains from PAF or iRBD patients differ from the ones of PD, DLB and MSA. In this regard, Singer and colleagues demonstrated the presence of α-syn in the CSF of most PAF cases included in the study, showing a similar amplification kinetic to PD and DLB cases, and significantly different from those with MSA ( 101 ). In addition, they observed that all PAF patients that later progressed toward MSA were the only ones showing amplification kinetics previously described in MSA patients ( 101 ).…”
Section: Introductionmentioning
confidence: 78%
“…In this regard, Singer and colleagues demonstrated the presence of α-syn in the CSF of most PAF cases included in the study, showing a similar amplification kinetic to PD and DLB cases, and significantly different from those with MSA ( 101 ). In addition, they observed that all PAF patients that later progressed toward MSA were the only ones showing amplification kinetics previously described in MSA patients ( 101 ). Thus, the use of amplification assays might constitute a potential diagnostic tool for MSA even at early-stages.…”
Section: Introductionmentioning
confidence: 78%
“…A very recent study prospectively followed a well-characterized cohort of PAF individuals to determine the role of α-synuclein oligomers and neurofilament light chain (Nfl) in cerebrospinal fluid as markers of phenoconversion [ 33 ]. As previously shown for the distinction of MSA from Lewy body disorders [ 36 ], higher Nfl measurements and lower maximum-thioflavin-fluorescence in the protein misfolding cyclic amplification (PMCA) assay of baseline cerebrospinal fluid accurately distinguished future phenoconversion to MSA versus Lewy body disorders or stable PAF [ 33 ].…”
Section: Isolated Autonomic Failurementioning
confidence: 99%